EFFECTS OF BABY MASSAGE USING LAVENDER AROMATHERAPY IN FULFILLMENT OF SLEEP NEED AMONG BABY AGE 6-12 MONTHS IN THE WORKING AREA NILAM SARI HEALTH CENTER BUKITTINGGI IN 2017 - Detty Afriyanti (Journal of Midwifery, 2018)
In Indonesia there is quite a lot of infants who have trouble in sleeping, that is 44.2%. If the infants's sleep requirement is not met, it can disrupt the growth and development of Infants. infants massage using lavender aromatherapy can contribute in improving infant's sleep needs. This study aims to determine the effect of infant massage using aromatherapy lavender to meet the needs of infants's sleep (6-12 months) at Nilam Sari Health Center in 2017. This study was Quasi Eksperiment with Two Group design. The study was conducted in June to July 2016 in the working area of Nilam Sari Health Center in Bukittinggi. The samples were 20 infants using purposive sampling technique. Data analysis was performed using T-Test dependent. Based on the results of the study, it was found that group I showed an average increase in infant sleep requirement between before and after massage of 2.55 hours. While the group II also showed an increase in the average of infant sleep requirement between before and after massage with lavender aromatherapy of 2.8 hours. The result of statistical test for both groups are the same, that is p value = 0.000 (p <0,05). The conclusion of this study asserting that there was an association between infant massage using aromatherapy lavender to fulfill the requirement of infant sleep (6-12 month) in the work area of Nilam Sari Health Center of Bukittinggi. It is hoped that the mothers can apply infant massage at home, since infant massage is very effective in improving infant’s sleep and more effectively using lavender aromatherapy.